PERANAN PENDIDIKAN INFORMAL DALAM MENDIDIK ANAK - Evie MPdH (Dharma Duta, 2017)
The old parents are the first and the main educator for the children to get the best prince or son. So why the old parents state as the first educator, because the son or the prince birth, growth, and develop in family (informal education). Then the old parents give the first education for the children in order to the children become to the best prince or the best son. The old parents stated as the main educator because the old parents give the main education for their children so become the best prince and the best son. The religion education is very important to the children in informal education. The old parents as the father and as the mother for the children so as the educators in family (informal education). The old parents can realize that very imfortant religion educatian for every member of their family. So They will give positive imfluence to growth and develop of their children. In the other side the children need to understand the religion education to increce the belive of the God, Tuhan Yang Maha Esa, Ida Sang Hyang Widhi Wasa.